Implementation Of Polluter Pays Principles As A Green Tax Policy In Realizing A Green Accounting - Umamah, Lidhatul (Buletin Ekonomika Pembangunan, 2023)
Tax is one of the State's revenues from several other revenues. Tax instruments are not only related to personal or corporate withdrawals of goods and their allocation, but taxes also talk about the impact on the surrounding environment. The term green tax will only be an algorithm, but requires regulations in the form of polluter pays principles that are fundamentally binding regarding sanctions that will be imposed on industry-specific companies. The research uses a descriptive qualitative method using literature review and data based on field studies conducted, so there will be a conclusion called the spearhead of the implementation of polluter pays principles. This research is also flexible as a new regulation in supporting the development of the green economy in general and the development of accounting specifically which is one of the benchmarks for Indonesia's economic growth.  Keyword: Tax, Polluter Pays Principles, Green Accounting